Alternative Exchange Rate Strategies and Fiscal Performance in Sub-Saharan Africa - Bazzoni, Stefania (IMF Working Papers; Working Paper ;, 1993)
This paper investigates the relationship between fiscal performance in 28 sub-Saharan African countries over the 1980-91 period with movements in the exchange rates, the terms of trade, and other macroeconomic aggregates. It finds that the tax base in most of these countries is heavily dependent on imports and import substitutes. Consequently, an overvaluation of the exchange rate in countries which adopted a fixed exchange rate strategy undermines the tax base and results in a widening of the fiscal deficit when the purpose of the strategy is to restore the real exchange rate to its equilibrium through fiscal contraction. Those countries which pursued a variable exchange rate strategy failed in attaining price stability, but exchange rate adjustment was critical in contributing to other macroeconomic objectives, particularly fiscal balance, competitiveness, and growth.